Intuition as a foundational human competence for creativity, ethics, and professional judgment in education in the age of artificial intelligence - Afrikanov , Lachezar (Journal of Education and e-Learning Research, 2025)
Intuition is often treated as an imprecise or secondary form of knowledge, yet research across psychology, neuroscience, and education demonstrates that it plays a central role in human judgment. In the context of artificial intelligence (AI), this capacity becomes increasingly significant as analytical and predictive tasks shift toward automated systems. The article explores intuition as a foundational human competence that supports creativity, ethical discernment, and rapid decision-making in complex environments. A narrative literature review was conducted to synthesize classical philosophical perspectives with recent empirical findings from cognitive science, neuroscience, professional studies, and human–AI interaction. Evidence shows that intuition operates as an embodied, experience-based process that enables individuals to recognize patterns, anticipate possibilities, and respond to uncertainty with contextual sensitivity. Studies further indicate that intuition improves through deliberate practice, feedback, and reflective learning. Recent work in human–computer interaction demonstrates that the most effective outcomes arise when intuitive human judgment is combined with algorithmic analysis, forming what scholars call hybrid intelligence. The article argues that intuition should be explicitly recognized within education and training as a learnable skill that complements analytical and digital literacies. Strengthening intuitive competence is essential for sustaining human agency, professional responsibility, and creativity in AI-rich environments.